Productivity, Capital Mobilization and Moral Hazard in Fisheries Share Contracts: Lake Nasser, Egypt - Finegold, Cambria; ., Mohamed Shehata; ., Olfat Anwar Habib (Journal of Social and Development Sciences, 2011)
As part of an international research project on reservoir fisheries productivity in developing countries, this paper examines contractual relations in the Lake Nasser fishery, seeking to understand why so many seemingly redundant contract types coexist and what effect they have on productivity. Based on the results of a socio-economic survey conducted in the fishery and drawing on the literature on agricultural sharecropping and share remuneration systems in fisheries, the paper analyses the roles of the different contracts observed in the Lake Nasser fishery. In particular, it discusses the incentives, limitations, and opportunities that these contracts offer to the different groups of actors (gear owners, license owners, crew members), and shows how these arrangements influence and shape the fishing strategies, capital mobilisation, and ultimately labour productivity of those different groups. While the debate on share contracts generally seeks to assess their efficiency relative to other types of contracts, this paper argues that the relevant question is not how efficient the contracts are, but what functions are served by the various co-existing contracts, and why different actors may choose each type. While the standard explanations of risk management and the impossibility of close supervision seem to provide some insight into this, it is also clear that the actors in the fishery use these contracts to mobilise capital and combine productive resources with other actors. This interlinking is a key function of the contracts, and the diversity of resource endowments and needs of the different actors helps explain the diversity of contract types.